The Spanish Army in Security Force Assistance - Guillermo López-Rodríguez (Revista Científica General José María Córdova, 2023)
This article analyses the lessons learned by the Spanish Army in the Security Force Assistance (SFA) Operation in Iraq between 2015 and 2020. The research uses primary data from 22 personal interviews conducted with Spanish officers and NCOs, as well as secondary data sourced from a database containing the Spanish Army’s online mission register. The results identify the scenarios and activities performed in SFA operations, as well as the main lessons learned by the Spanish Army in Iraq. The two main lessons are the prevention of internal attacks and the relevance of awareness of cultural dimensions to improve training processes. Conclusions can be extrapolated to other European armies, providing policy recommendations for training local forces in SFA operations.